Structural Characterization and Infrared and Electrical Properties of the New Inorganic-Organic Hybrid Compound [N(C3H7)4]2[Hg2Cl6]. (18th October 2012) - Oueslati, A.; Chaabane, I.; Adil, K.; Hlel, F.
Abstract : New inorganic-organic hybrid [(C3 H7 )4 N]2 Hg2 Cl6 compound was obtained and characterised by single-crystal X-ray diffraction, infrared, and impedance spectroscopy. The latter crystallizes in the monoclinic system (space group C 2/ c, Z = 8 ) with the following unit cell dimensions: a = 18.489 (1) Å, b = 13.0419 (6) Å, c = 29.162 (2) Å, and β = 91.686 ∘ (2). Besides, its structure was solved using 84860 independent reflections leading to R = 0.038 . Electrical properties of the material were studied using impedance spectroscopic technique at different temperatures in the frequency range of 209 Hz to 5 MHz. Detailed analysis of the impedance spectrum suggested that the electrical properties of the material are strongly temperature-dependent. The Nyquist plots clearly showed the presence of bulk and grain boundary effect in the compound.